Modeling Heat Transfer in Cylindrical Batteries: Spiral-Based Thermal Conductivity Tensor - Hvožďa, Jiří; Boháček, Jan; Vakhrushev, Alexander; Karimi-Sibaki, Ebrahim (Avestia Publishing, 2025)
This study investigates the importance of considering the well-known spiral structure of cylindrical batteries in numerical models of heat transfer. Such models typically simplify the internal geometry by a concentric layout of electrodes and separators, resulting in an effective orthotropic thermal conductivity with radial, tangential, and axial components defined in a cylindrical coordinate system. However, the actual spiral structure suggests radius-dependent thermal conductivity. In this study, several thermal simulations were performed, comparing thermal fields obtained with the commonly used cylindrical orthotropy and a more realistic spiral structure. The results show that the spiral structure has a negligible effect on the overall temperature distribution for configurations with dense spirals and higher radial thermal conductivity (2 W·m1·K1). However, for lower radial thermal conductivity (0.2 W·m1·K1), considerable errors were observed even for dense spirals. These findings emphasize the need for studies to justify simplifications made in the thermal conductivity tensor.

This study investigates the importance of considering the well-known spiral structure of cylindrical batteries in numerical models of heat transfer. Such models typically simplify the internal geometry by a concentric layout of electrodes and separators, resulting in an effective orthotropic thermal conductivity with radial, tangential, and axial components defined in a cylindrical coordinate system. However, the actual spiral structure suggests radius-dependent thermal conductivity. In this study, several thermal simulations were performed, comparing thermal fields obtained with the commonly used cylindrical orthotropy and a more realistic spiral structure. The results show that the spiral structure has a negligible effect on the overall temperature distribution for configurations with dense spirals and higher radial thermal conductivity (2 W·m1·K1). However, for lower radial thermal conductivity (0.2 W·m1·K1), considerable errors were observed even for dense spirals. These findings emphasize the need for studies to justify simplifications made in the thermal conductivity tensor.
Modeling Heat Transfer in Cylindrical Batteries: Spiral-Based Thermal Conductivity Tensor
Keywords: Battery thermal management systems; Li-Ion cylindrical batteries; orthotropic thermal conductivity; spiral structure.; Battery thermal management systems; Li-Ion cylindrical batteries; orthotropic thermal conductivity; spiral structure.